BOOK REVIEW: MAJAPAHIT IN TWO PERSPETIVES - Sektiadi Sektiadi (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2016)
The two books mentioned above were published in conjunction with a seminar on Majapahit, commemorating its 721st anniversary. The great kingdom indeed withheld mysteries that have always been discussed since the late 19th century. At the least it was noted that N.J. Krom reported the relics of the kingdom two hundred years ago. The following intensive studies generated enough knowledge about this area, but they also presented the myths because not the studies could not unfold every aspect of the kingdom. These included the authorities in the kingdom’s era as well as other figures who ever lived in this region. Manuscripts such as Nagarakretagama have made scholarly and everyday discussions more interesting by making connections various aspects of the texts with archaeological findings in Trowulan area.